The Symbol Digit Modalities Test (SDMT) is sensitive but non-specific in MS: Lexical access speed, memory, and information processing speed independently contribute to SDMT performance - Sandry, Joshua; Simonet, Daniel V.; Brandstadter, Rachel; Krieger, Stephen; Katz Sand, Ilana; Graney, Robin A.; Buchanan, Alexandra V.; Lall, Sophia; Sumowski, James F. (Multiple sclerosis and related disorders, 2021)
•The symbol digit modalities test (SDMT) is the most widely used assessment of cognition in multiple sclerosis and commonly interpreted as a measure of information processing speed.•The SDMT is not process pure and measures multiple cognitive processes, including memory, lexical access speed and information processing speed.•The SDMT should be interpreted and referred to as a general measure of cognition rather than a specific test of information processing speed. The Symbol Digit Modalities Test (SDMT) is the most sensitive metric of neurocognitive function in multiple sclerosis (MS), and is consistently interpreted as a measure of information processing speed (IPS). To evaluate the cognitive psychometric profile captured by the SDMT to identify whether different cognitive processes independently underlie performance. Three samples of MS patients (total n=661; 185 research patients at MS center; 370 clinical patients at MS center; 106 persons with MS from the community) completed objective assessments of neuropsychological function across cognitive domains. Exploratory factor analysis (EFA) was used to derive latent cognitive factor scores, and operationalize cognitive domain composite scores, to understand the unique, shared and redundant contribution of different cognitive domains to SDMT performance using hierarchical multiple regression and commonality analysis. Across three independent samples we provide converging strong evidence that the cognitive domains of Memory, IPS and Rapid Automatized Naming (lexical access speed) jointly and uniquely contribute to SDMT performance. The SDMT measures multiple cognitive processes, which likely explains the high degree of sensitivity to cognitive change in MS. Researchers and clinicians should interpret the SDMT as a multifarious measure of general cognition rather than a specific test of IPS.